Boundary Objects as the Missing Link in the Orchestration of Resources: An Exploratory Study of Dassault Aviation Mirage IV and Rafale Programs - Versailles, David; Mérindol, Valérie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
In this contribution, we investigate the use of boundary objects (Star and Griesemer) for the orchestration of resources (Teece). We propose a comparative case study elaborating on two Dassault Aviation military fighters under an abductive approach. In this contribution, we elaborate on the micro-foundations approach. Our contribution discusses several properties of boundary objects in relation with the orchestration of resources: type, granularity, openness, malleability, and completeness. We conclude that boundary objects are critical to orchestration. Their properties explain why they diversely impact on sensing, seizing and reconfiguring. They elaborate on knowledge articulation and teamwork, and require specific ways of working.